Dampak Pembelajaran Kurikulum Merdeka Di SD Jam’iyatul Washliyah - Daulay, Afrahul Fadhila; Azzahra, Lathifah; Hasibuan, Appuannisa; Andina, Fadillah; Habibah, Azizatul; Karniawan, Fatimah Zahara (Peneliti.net, 2024)
The Merdeka Belajar curriculum is an innovation in Indonesian education which aims to develop students' learning potential and interest. The aim of the independent curriculum is to improve the quality of learning, form independent student character, and reduce gaps in education. This research uses a qualitative research design. This research aims to determine the impact of implementation, positive impacts and negative impacts of the independent curriculum implemented at SD Al-Jama'iyah.